2011
DOI: 10.5005/jp-journals-10024-1038
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Turmeric and Chlorhexidine Gluconate Mouthwash in Prevention of Plaque Formation and Gingivitis: A Clinical and Microbiological Study

Abstract: Aim To compare the efficacy of turmeric mouthwash and chlorhexidine gluconate mouthwash in prevention of gingivitis and plaque formation. Materials and methods A total of 100 randomly selected subjects visiting the Department of Periodontology at Bharati Vidyapeeth Deemed University, Dental College and Hospital, were considered for the study. The gingival index (GI) by Loe and Silness was recorded which was followed by Turesky- Gilmore-Glickman modification of Quigley Hein plaque index (TQHPI) at 0, 14 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(41 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…Other than the in vitro experiments mentioned, researchers have also assessed these methods in vivo. Waghmare et al 26 evaluated the effects of CHX and curcumin mouthwashes in prevention of plaque formation and inflammation in 2011. Their results suggested these mouthwashes as effective complementary measures alongside mechanical removal for periodontal diseases, showing a comparable effect between curcumin and CHX.…”
Section: Discussionmentioning
confidence: 99%
“…Other than the in vitro experiments mentioned, researchers have also assessed these methods in vivo. Waghmare et al 26 evaluated the effects of CHX and curcumin mouthwashes in prevention of plaque formation and inflammation in 2011. Their results suggested these mouthwashes as effective complementary measures alongside mechanical removal for periodontal diseases, showing a comparable effect between curcumin and CHX.…”
Section: Discussionmentioning
confidence: 99%
“…Waghmare PF et al, compared the turmeric and chlorhexidine gluconate mouthwash in the prevention of plaque formation and gingivitis: a clinical and microbiological study [11]. Gottumukkala et al, studied the effectiveness of subgingival irrigation of indigenous 0.1% curcumin solution on clinical and microbiological parameters patients: A pilot randomised clinical trial [12].…”
Section: Discussionmentioning
confidence: 99%
“…15- 20 Sari E et al 16 evaluated the effects of 0.2% chlorhexidine gluconate on streptococcus mutans and lactobacilli levels in saliva. They reported that in combination with mechanical plaque removal, 0.2% chlorhexidine gluconate is an important therapeutic agent in controlling the streptococcus mutans and lactobacilli levels of orthodontic patients with fixed appliances.…”
Section: Discussionmentioning
confidence: 99%